Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Pt Sucofindo Cabang Padang Dan Burnout Sebagai Variabel Mediasi - Sihotang, Hendro Hotni Rohana; Maryanti, Eka (CV. ITTC INDONESIA, 2025)
This research aims to determine the effect of the work environment on the performance of employees at PT Sucofindo Padang Branch, with burnout as a mediating variable. The population in this study consisted of 40 employees of PT Sucofindo Padang Branch, with sample selection using total sampling, resulting in a sample size of 40 individuals. Data were collected through the distribution of questionnaires, subsequently processed and tested using SmartPLS 4.0. The findings of the research, based on the results of hypothesis testing, indicate that: 1) burnout has a positive and significant effect on performance, 2) the work environment has a positive and significant effect on burnout, and 3) the work environment has a positive and significant effect on employee performance. Job satisfaction is capable of mediating the influence of the work environment on employee performance.